Skin Autofluorescence, as a Measure of AGE Accumulation in Individuals Suffering from Chronic Plaque Psoriasis - Karolina Kopeć-Pyciarz; Irena Makulska; Danuta Zwolińska; Łukasz Łaczmański; Wojciech Baran (Mediators of Inflammation)
Background. Psoriasis is currently regarded as a chronic systemic inflammatory disease associated with increased cardiovascular risk. Advanced glycation end products (AGEs) contribute to the development of atherosclerosis. Objectives. The aim of the study was the assessment of skin autofluorescence (SAF), as a measure of AGE accumulation, in individuals suffering from chronic plaque psoriasis without any comorbid conditions. Methods. A study group consisted of 70 patients with chronic plaque psoriasis without any comorbid conditions and 59 healthy controls, matched by age and gender. AGE accumulation was assessed by SAF (AGE Reader, DiagnOptics BV) which is a validated and noninvasive technique. Relations between SAF and some clinical and laboratory data were assessed. Results. SAF was positively correlated with age both in patients with psoriasis and controls (R=0.722, p<0.00001 and R=0.613, p<0.00001, respectively). There was significantly increased SAF in patients with psoriasis with elevated levels of C-reactive protein (CRP) and increased erythrocyte sedimentation rate (ESR) compared to controls (p<0.00001; p<0.00001, respectively, after adjustment to age). Increased SAF was found in psoriatic patients with prediabetes (HbA1c 5.7–6.4%) compared to controls (p<0.0012, after adjustment to age). Conclusion. Systemic inflammation (increased CRP level), prediabetes, and aging may influence enhanced AGE accumulation in patients with psoriasis without any comorbidities. SAF may be considered as a useful, noninvasive method to identify patients with psoriasis at increased cardiovascular risk.